The level of body balance in standing position and handstand in seniors athletes practicing artistic gymnastics - Puszczalowska-Lizis, E.; Omorczyk, J. (Acta of Bioengineering and Biomechanics, 2019)
Purpose: The aim of the study was to compare the values of selected stability indices registered in the trials in a standing with eyes open and without visual control and in handstand in athletes practicing gymnastics at the highest level of advancement. Methods. The study included 20 athletes practicing gymnastics. The research tool was posturograph CQ-Stab 2P. The results obtained in individual trials were compared using Friedman repeated measures analysis of variance by ranks, and then subjected to Dunn post-hoc test with Bonferroni adjustment. Results: Statistically significant variation in the values of stability indices recorded in individual samples were found. Exceptions are the results obtained in the trials with eyes open and without visual control with regard to the size of the surface area delineated by the COP (p=0.173) and the frequency of corrective reactions (p=0.464), as well as the length of the statokinesiogram path in the mediolateral direction (p=0.342), mean velocity of COP movement in the mediolateral direction (p=0.246), maximal amplitude of the COP in the mediolateral direction (p=0.342) and number of COP displacements in the mediolateral direction (p=0.246). Conclusions: In seniors, disabling visual control during free standing, as well as adopting a handstand position, results in deterioration of the stability indices which is a resultant of the COP displacement in both directions, as well as in the anteroposterior direction. Lack of differences in the values of stability indices in the mediolateral direction suggest that in a free standing position, seniors practicing gymnastics control the movement of the center of foot pressure in the mediolateral direction and eye control is not important for the stability of the body in the frontal plane.